A retrospective study of poisoning deaths from forensic autopsy cases in northeast China (Liaoning). (April 2019) - Wang, Lin-Lin; Zhang, Miao; Zhang, Wei; Li, Bing-Xuan; Li, Ru-Bo; Zhu, Bao-Li; Wu, Xu; Guan, Da-Wei; Zhang, Guo-Hua; Zhao, Rui
Abstract: Acute poisoning is a public health threat that leads to morbidity and mortality worldwide. In this retrospective study, we evaluated autopsies from deaths caused by acute poisoning from 2008 to 2017 at the School of Forensic Medicine, China Medical University (SFMCMU) in the Liaoning Province, northeast China. A total of 140 poisoning deaths were investigated and the demographic characteristics, causes and manner of death, toxics category were analyzed. The number of poisoning deaths gradually increased during the study period. The majority of poisoning deaths were accidents (66.43%), followed by suicides (27.86%), and homicides (3.57%). Of the 140 cases, 47 (33.57%) were caused by drugs, 38 (27.14%) by agrochemicals (mainly organophosphate pesticides, n = 16), 37 (26.43%) by respiratory dysfunction toxics (mainly carbon monoxide, n = 21), and 9 (6.43%) by poisonous plants and animals. Alcohol/methanol (5, 3.57%) and other chemicals (4, 2.86%) accounted for the remaining cases. The present study provides poisoning distribution in the Liaoning province and highlights implications for public health policy and prevention efforts in northeast China. Highlights: Poisoning deaths from forensic autopsy cases in northeast China (Liaoning Province) were retrospectively analyzed. The majority of poisoning deaths in the Liaoning Province were accidents. Victims aged 20 to 49 accounted for more than 60% of the deceased. Drugs and agrochemical poisoning accounted for more than half of the poisoning cases in the Liaoning Province.